2015
DOI: 10.1016/j.eucr.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Penile Replantation After Five Hours of Warm Ischemia

Abstract: Although a rare occurrence, this event may occur as a result of self-mutilation among individuals with psychiatric disturbances or due to work-related accidents, iatrogenic injuries or the actions of individuals motivated by jealously, rage and feelings of betrayal. In western societies, most penile amputations are the result of self-aggression during a psychotic episode, the treatment of victims involves resuscitation, stabilization and immediate psychiatric support. The amputated tissue must be preserved und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Previous reports suggested that a critical factor for a successful replantation is the adequacy of venous outflow and the superficial and deep dorsal veins play an important role. 6 , 7 In the present case, identification and anastomosis of the superficial and deep dorsal veins were not so difficult due to their large diameter. However, the most difficult issue in this replantation was the reconstruction of arteries.…”
Section: Discussionmentioning
confidence: 63%
“…Previous reports suggested that a critical factor for a successful replantation is the adequacy of venous outflow and the superficial and deep dorsal veins play an important role. 6 , 7 In the present case, identification and anastomosis of the superficial and deep dorsal veins were not so difficult due to their large diameter. However, the most difficult issue in this replantation was the reconstruction of arteries.…”
Section: Discussionmentioning
confidence: 63%
“…Skin venous congestion leading to necrosis occurs in over half of all penile replantations and is the most common complication. 3,6,20 The reason for such a high complication rate lays in the high variability of venous and arterial supply to the skin; arterial blood flow is provided by the external pudendal arteries, which branch early into smaller vessels, before the penis, making arterial re-anastomosis of the skin's arterial supply difficult if not impossible. 21 Medical leach therapy was attempted given the prior success reported by others to treat venous congestion after penile replantation.…”
Section: Discussionmentioning
confidence: 99%
“…That technique incorporates a structural approach to the penis without any neurovascular repair. Despite satisfactory functional and cosmetic results, skin necrosis is generalized [ 11 ]. By and large, macroscopic replantation techniques have been employed with good postoperative results [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, microscopic replantation seems to afford better chances of organ survival and lower complication rates, although statistically convincing evidence remains unavailable. The disadvantages of the technique, however, include the requirement of skill and equipment for such procedures that may be unavailable in places with few resources or, at times, in emergency situations [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation